Solutions for submucosal injection in endoscopic resection: a systematic review and meta-analysis - Ferreira, Alexandre Oliveira; Moleiro, Joana; Torres, Joana; Dinis-Ribeiro, Mario (Endoscopy International Open, 2016)
Background and aims: Submucosal injection is standard practice in endoscopic mucosal resection of gastrointestinal lesions. Several solutions are used. Our aim was to systematically review their efficacy and safety.Patients and methods: We performed a systematic review and meta-analysis using a random effects model of randomized controlled trials (RCTs) from MEDLINE. Studies in animal models were qualitatively assessed for efficacy and safety.Results: In total, 54 studies were qualitatively assessed. Eleven RCTs were analyzed, two of which were on endoscopic submucosal dissection (ESD). The quantitative synthesis included nine RCTs on endoscopic mucosal resection (EMR), comprising 792 subjects and 793 lesions. Mean lesion size was 20.9 mm (range 8.5 – 46 mm). A total of 209 lesions were randomized to sodium hyaluronate (SH) vs normal saline (NS), 72 to 50 % dextrose (D50) vs NS, 82 to D50 vs SH, 43 to succinylated gelatin, 25 to hydroxyethyl starch and 36 to fibrinogen. In total, 385 were randomized to NS as controls. NS and SH are the best studied solutions and seem to be equally effective in achieving complete resection (OR 1.09; 95 %CI 0.82, 1.45). No solution was proven to be superior in complete resection rate, post-polypectomy bleeding or coagulation syndrome/perforation incidence. Many solutions have been tested in animal studies and most seem more effective for mucosal elevation than NS.Conclusions: There are several solutions in clinical use and many more under research, but most are poorly studied. SH seems to be clinically equivalent to NS. There are no significant differences in post-polypectomy complications. Larger RCTs are needed to determine any small differences that may exist between solutions.